Relating Country-Level Governance and Tree Cover Loss in Sub-Saharan African Protected Areas: Identifying Knowledge Gaps and a More Nuanced Perspective - Dehmel, Naira; Franks, Phil; Schreckenberg, Kate; Beresford, Alison; Buchanan, Graeme; Dawson, Terence P. (Frontiers in Forests and Global Change, 2022)
‘Good governance’ is highlighted by many as being essential for improving protected area (PA) management and conservation outcomes, with a growing body of evidence based on site-level governance data. Yet how exactly governance at other levels supports or hinders successful PA implementation, and how this should be considered in conservation planning and practice, remains insufficiently understood. We conducted an exploratory analysis of the relationship between the quality of country-level governance and trends in tree cover loss within sub-Saharan African PAs. For the period 2008–2017, we correlated annual governance scores from the Ibrahim Index of African Governance (IIAG) with the annual rate of tree cover loss in the total terrestrial area of PAs in 33 forested sub-Saharan African countries. Overall governance was not correlated with tree cover loss in a simple model, but there was evidence that overall governance was positively correlated with tree cover loss in PAs when the interaction with environmental governance was included. The interaction indicated that the rate of tree cover loss decreased for a given level of overall governance as environmental governance increased. Human development was negatively correlated with forest loss. Thus, the relationship between country-level ‘good governance’ and conservation success is more complex than a direct and positive cause and effect. Yet, uncertainty remains about the many possible and likely confounding pathways: whilst the quality of overall governance may be mirrored at the site-level, it may also contribute to increased anthropogenic pressures on natural resources. Through this research we found significant limitations in data quality and availability both to evaluate the effectiveness of protection beyond tree cover, as well as less conventional governance aspects, such as environmental policy and regulation or site-level governance. With an expected increase in area-based protection and conservation financing in the coming decades, such data will be vital to monitor the effectiveness of our efforts and ensure financial accountability.